The Regeneration Crisis and Traditional Packaging of Garut Wajit: A Threat to Sundanese Culinary Cultural Identity - Nisa Nurul Kamila; Arash Ahira; Reisya Nabila Putri; Tenti Fauziah; Itto Turyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Wajit Garut is a traditional food originating from Garut Regency, West Java, which has been produced for generations using local ingredients and wrapped in natural corn leaves as a marker of Sundanese cultural identity. In the face of modernization, changes in values between generations, and the impact of the COVID-19 pandemic, two interrelated issues have emerged: (1) the challenge of regeneration that threatens the sustainability of traditional knowledge, and (2) the potential degradation of packaging from natural materials to synthetic materials that erode the values of local wisdom. This study uses a qualitative descriptive method through direct field observation and in-depth interviews with Ibu Dini, the founder and sole home-based wajit producer that has been operating since 2012 in Garut Regency. The results show that wajit production is highly dependent on certain irreplaceable ingredients, especially brown sugar from Bungbulang and traditional production techniques, with corn leaf packaging that has functions and cultural values that cannot be replaced by plastic. The challenge of regeneration is clearly evident even though Ibu Dini's children have begun to help and learn the production process, but the commitment to continue the business has not yet been formed. The study also confirmed that the performance of wajit (rice cake) MSMEs is influenced by product quality, innovation capacity, and local government support.